P.145 Perceived Limits of Endovascular Treatment for Secondary Medium Vessel Occlusion Stroke. (November 2021) - McDonough, RV; Cimflova, P; Kappelhof, M; Singh, N; Kashani, N; Ospel, JM; Demchuk, A; Menon, B; Chen, M; Sakai, N; Fiehler, J; Goyal, M
Abstract : Background: Thrombus embolization during endovascular treatment (EVT) occurs in up to 9% of cases, making secondary medium-vessel occlusions (MeVOs) of particular interest to neurointerventionalists. We sought to gain insight into the current EVT approaches for secondary MeVO stroke in an international case-based survey as there are currently no clear recommendations for EVT in these patients. Methods: Participants were presented with three secondary MeVO cases, each consisting of three case-vignettes with changes in patient neurological status (improvement, no change, unable to assess). Clustered multivariable logistic regression analyses were used to assess factors influencing the decision to treat. Results: 366 physicians from 44 countries took part. The majority (54.1%) were in favor of EVT. Participants were more likely to treat occlusions in the anterior M2/3 (74.3%; risk ratio [RR]2.62, 95%CI:2.27-3.03) or A3 (59.7%; RR2.11, 95%CI:1.83-2.42) segment, compared to the M3/4 segment (28.3%;reference). Physicians were less likely to pursue EVT in patients with neurological improvement (49.9% versus 57.0%; RR0.88, 95%CI:0.83-0.92). Interventionalists and more experienced physicians were more likely to treat secondary MeVOs. Conclusions: Physician's willingness to treat secondary MeVOs endovascularly is limited and varies per occlusion location and change in neurological status. More evidence on the safety and efficacy of EVT for secondary MeVO stroke is needed.